Not everything that is faced can be changed. But nothing can be changed until it is faced: The privatisation of the Cyprus International Airports and its impact on the workforce. - Charalambous, Vicky (2008)
It is commonly known that organisational change programmes do not always produce the desirable results. Nevertheless, change and adaptation is vital for a company to survive in today's highly evolving and demanding environment. Empirical studies, however, have reported high failure rates in the attempts of organisational transformation plans to deliver their intended goals and objectives. Wider literature on organisational change has many accounts of negative reactions by the parties affected by the change, indicating that the success of any change proposal depends on the correct diagnosis of the obstacles, as well as the choice of the strategic path. This paper explores the change strategies and practices that were used during the transformation of the International Airports in Cyprus, focusing on the impact that the use of different strategic routes had on the Airport employees. Based on extensive in-depth interviews with Airport employees and trade union officials, this paper provides an exploratory study, with a humanistic focus on the workforce, of the privatisation process of the Airports in Cyprus and presents this in the context of theoretical frameworks on organisational change management. Findings indicate that the change agents used different methods to achieve the commitment of employees and the compliance of the trade unions. The research results are congruent with literature which suggests that fostering change does not just increase understanding and acceptance of the change process on behalf of the employees, but also increases the efficiency and productivity of the organisation as a whole. The implications of the findings are discussed in detail.